Real‐life effectiveness of MP‐AzeFlu in Irish patients with persistent allergic rhinitis, assessed by visual analogue scale and endoscopy. Issue 4 (11th October 2018) - Kaulsay, Ranbir; Nguyen, Duc Tung; Kuhl, Hans Christian
Abstract: Introduction: Most allergic rhinitis (AR) patients have moderate‐to‐severe, persistent disease. Meda Pharma's AzeFlu (MP‐AzeFlu) combines intranasal azelastine hydrochloride (AZE) and fluticasone propionate (FP) in a novel formulation in a single device to treat AR. This prospective, noninterventional study sought to assess the effectiveness of MP‐AzeFlu (one spray/nostril twice daily; 548 µg AZE/200 µg FP daily dose) in relieving AR symptom severity. Methods: A visual analogue scale (VAS) was used prior to MP‐AzeFlu treatment on days 0, 1, 3, 7, 14, 21, 28, 35, and 42 by 53 persistent AR (PER) patients seen in routine clinical practice in Ireland. An endoscopy was performed on days 0 and 28, and symptoms of edema, discharge, and redness were scored on a three‐point scale (for both nostrils). Results: Patients using MP‐AzeFlu experienced rapid VAS score reduction from 73.4 mm (standard deviation [SD], 20.3) at Day 0 to 31.5 mm (SD, 25.0) at day 28 ( P < 0.0001) to 28.1 mm (SD, 24.1) at day 42 ( P < 0.0001), a 45.3‐mm reduction. On average, patients achieved a clinically relevant VAS score cutoff of 50 mm before Day 7. Total endoscopy score decreased from 7.5 mm (SD, 3.1) at baseline to 3.5 mm (SD, 2.5) at Day 28. The incidence of severe edema on endoscopy decreased from 53.1% at baseline to 3.8% at Day 28. A similar reduction in the incidence of thick/mucousy discharge (from 28.3% to 4.8%) and severe redness (from 34.9% to 0%) was also observed. Conclusions: MP‐AzeFlu provided effective, rapid control of PER as assessed by VAS in a real‐world clinical setting in Ireland. Symptom improvement was observed at Day 1, sustained for 42 days, and associated with improved mucosal appearance after 28 days. These results confirm the safety of MP‐AzeFlu and exceed the efficacy demonstrated in phase 3 clinical studies for controlling AR in PER patients. Abstract : Meda Pharma's AzeFlu (MP‐AzeFlu) comprises intranasal azelastine hydrochloride and fluticasone propionate in a novel formulation delivered in a single device. In this noninterventional prospective study, patients from a routine clinical practice in Ireland were prescribed MP‐AzeFlu and followed for 42 days. MP‐AzeFlu provided effective and rapid control of persistent allergic rhinitis in this real‐world clinical setting.